Additional prognostic value of vasodilator stress CMR in patients with inconclusive stress test to detect coronary artery disease. (8th February 2021) - Pezel, T; Bonnet, G; Garot, P; Asselin, A; Unterseeh, T; Champagne, S; Hovasse, T; Kinnel, M; Sanguineti, F; Garot, J
Abstract: Funding Acknowledgements: Type of funding sources: None. BACKGROUND: Guidelines recommend performing a non-invasive testing for ischemia to diagnose coronary artery disease (CAD). However, these tests are frequently inconclusive (25%). This population has been poorly studied because of its heterogeneity. In such cases, stress cardiac magnetic resonance (CMR) may be useful to improve diagnostic certainty. To date, no study has evaluated the prognostic value of stress CMR in these patients presenting with prior inconclusive test. PURPOSE: To assess the additional prognostic value of vasodilator stress perfusion CMR in patients with a first inconclusive stress test to detect CAD. METHODS: Between 2008 and 2018, consecutive patients with inconclusive stress test prospectively referred for vasodilator stress perfusion CMR with dipyridamole were followed for major adverse cardiovascular events (MACE) defined as cardiac death or myocardial infarction. Inconclusive stress test was defined by echocardiography or nuclear stress testing with uncertain conclusion about the diagnosis of CAD. To characterize this population, an unsupervised clustering analysis was performed using 18 variables. Univariable and multivariable Cox regressions were performed to determine the prognostic value of inducible ischemia by stress CMR in each cluster. RESULTS: Of 1502 patients with inconclusive stress test (62 ± 12 years, 59% men), 1441 (96%) completed the CMR protocol and 1397(93%) completed the follow-up (median 5.5 ± 2.3 years). Stress CMR was well tolerated without occurrence of death or severe adverse event. The clustering analysis identified 3 clusters: Cluster 1 (n = 524, 35%) had the highest prevalence of previous percutaneous coronary intervention (PCI), the highest presence of myocardial scar on CMR, the lowest LVEF(35 ± 7%) and the highest degree of LV dilatation. Cluster 2 (n = 406, 27%) had the highest prevalence of previous coronary artery bypass grafting (CABG), preserved LVEF(54 ± 10%), absence of LV dilatation and rate of male(89%). Cluster 3 (n = 572, 38%) had the lowest rate of previous PCI/CABG and of myocardial scar. This cluster gathered the oldest patients (73 ± 11 years), predominantly female (60%), with the highest rate of atrial fibrillation and body mass index. Survival analysis found significant differences across clusters for the occurrence of MACE (p = 0.02). Moreover, inducible ischemia was significantly associated with the occurrence of MACE in each cluster (cluster 1, HR 2.28; [95%CI: 1.31-3.99]; p = 0.0028; cluster 2, HR 3.37; [95%CI, 1.97-5.75]; p < 0.0001; cluster 3, HR 2.73; [95%CI, 1.67-4.46]; p < 0.0001). In multivariable Cox regression, inducible ischemia was an independent predictor of a higher incidence of MACE in each cluster (p < 0.001). CONCLUSIONS: Cluster analysis identified 3 different phenotypes of patients with inconclusive stress test that were associated with distinct clinical and prognostic profiles. Within these clusters, CMR stress has an additional prognostic value to predict the occurrence of MACE.